EFFECT OF THE USE OF PLAIN YOGURT IN VARIOUS LEVEL PRODUCT QUALITY AS A STARTER ON HOMEMADE YOGURT - Isai Kobak (Jurnal Sains Peternakan, 2014)
The study was conducted on December 6, 2013 until January 6, 2014 in Laboratory of the Faculty of Animal Husbandry, University of Malang Kanjuruhan, carried aim of this study was to determine the effect of using plain yogurt as a starter at various levels of product quality homemade yogurt. The material used in this study was fresh milk, skim milk, plain yogurt as a starter, which consists of the bacteria Streptococcus thermophilus and Lactobacillus bulgaricus. The research method used was a laboratory experiment using a completely randomized design (CRD). Observed variables, namely pH, protein content and organoleptic quality ifthe translating  treatment effect then proceed with the LSD test. repeated 3 times. The investigations P1 treatment +100 ml milk plain yogurt milk P2 tratment +150 ml milk plain yogurt milk. P3 tratment +200 ml milk plain yogurt milk yogurt plain. The results showed that treatment research that P1 (100 ml) P2 (150 ml) and P3 (200 ml) using plain yogurt as a starter no effect (P> 0.05) on the pH content. Level starter 100, 150, 200 ml, yielding average values of 4.33 and 4.00 pH 4.67, at room temperature. and there is no effect (p> 0,05) the protein content and protein content and organoleptic average of 4.18% 4.21% and 4.24%.Keywords: yogurt , plain , homemade yogurt Starter